Implant comparisons for finishing steers - Laudert, S.; Kuhl, Gerry L.; Walker, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A one hundred and forty day field trial was conducted to evaluate the relative performance of steers implanted with Compudose, Ralgro and Synovex-S. Daily gains of cattle receiving a single initial implant were increased 8.0% with Compudose, 12.7% with Ralgro and 21.5% with Synovex-S compared to non-implanted controls. Steers on a reimplant program with Ralgro and/or Synovex-S gained 23.6 to 24.9% faster than controls, with no significant difference due to implant brand or sequence.
Keywords: Beef; Implant; Performance; Gain